An Unusual Case Report of Iatrogenic Metrorrhagia and Hematochezia Following Itraconazole - Yashaswi Rai (Wolters Kluwer Medknow Publications, 2024)
Itraconazole is an effective triazole antimycotic drug that has a desirable pharmacokinetic profile to combat various fungal pathogens. It acts by inhibiting ergosterol biosynthesis in fungal cell membranes. Itraconazole is not totally selective toward Cytochrome P450 family 3 subfamily A member 4 (CYP450 3A4), but exhibits the most potent inhibition of CYP450 3A4. Thus, these drugs interfere with CYP450 3A4 proteins expressed in the liver, intestine, kidney, adrenals, ovary, and testis. We present a case report of metrorrhagia and hematochezia following intake of itraconazole, a commonly used azole drug against dermatophytic infection. This article strongly highlights eliciting menstrual history and gynecological- and surgical-related problems before prescribing itraconazole. Also, to be aware of the vaginal bleeding being the unusual side effects of itraconazole.